Dynamique narrative du texte, du film et de la musique - Wolfgang Wildgen (Cahiers de Narratologie)
Narrativity is basically linked to the dynamics of the events and actions which are told and it depends on the pragmatic context, mainly on the narrator and his audience, i.e. on the discursive setting. These dynamics ask for an adequate theoretical frame, e.g. in the format of dynamical system theory or vector analysis. Furthermore, narrativity can be manifested in different modalities. We shall present some specimens of analysis in the linguistic modality (spontaneous oral tales, folktales), in the visual modality (painting by Leonardo da Vinci, action movie in the series of Bond films), and in the musical modality (Blues music). The static analyses in the tradition of structuralism are replaced by morphodynamic schemes, by gesture and glance vectors, paths of pursuit and scenarios of conflict in action movies and eventually by harmonic sequences in the Blues. In this dynamic perspective, the notion of narrativity gains a different profile and it is freed from the preference for linguistic or logical categories.